2010
DOI: 10.2353/ajpath.2010.090605
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference Against Hepatic Epidermal Growth Factor Receptor Has Suppressive Effects on Liver Regeneration in Rats

Abstract: Liver regeneration after a two-thirds partial hepatectomy (PHx) is a complex process requiring interaction and cooperation of many growth factors and cytokines and cross talk between multiple pathways. Along with hepatocyte growth factor and its receptor MET (HGF-MET), the epidermal growth factor receptor (EGFR) signaling pathway is activated within 60 minutes after PHx. To investigate the role of EGFR in liver regeneration, we used two EGFR-specific short hairpin silencing RNAs to inhibit EGFR expression in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
49
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 67 publications
8
49
0
Order By: Relevance
“…The activities of physiological processes reflected by the expression changes were analyzed then by systems biology methods, and both growth factor branches and its regulation of hepatocyte proliferation activity were elevated in rat liver regeneration (Figure 1). The above results were consistent with those of other authors (Gezginci-Oktayoglu et al, 2010;Paranjpe et al, 2010;Gui et al, 2011;Tsai and Wang, 2011;Wu et al, 2011), who demonstrated the correlation between the signal transduction activity of the growth factor branch of the NF-κB signaling pathway and hepatocyte proliferation activity. The above results helped deduce the following possible connection between the growth factor branch and hepatocyte proliferation activity.…”
Section: Discussionsupporting
confidence: 93%
“…The activities of physiological processes reflected by the expression changes were analyzed then by systems biology methods, and both growth factor branches and its regulation of hepatocyte proliferation activity were elevated in rat liver regeneration (Figure 1). The above results were consistent with those of other authors (Gezginci-Oktayoglu et al, 2010;Paranjpe et al, 2010;Gui et al, 2011;Tsai and Wang, 2011;Wu et al, 2011), who demonstrated the correlation between the signal transduction activity of the growth factor branch of the NF-κB signaling pathway and hepatocyte proliferation activity. The above results helped deduce the following possible connection between the growth factor branch and hepatocyte proliferation activity.…”
Section: Discussionsupporting
confidence: 93%
“…We show that the induction of AR protein is abrogated in ADAM17 h-KO mice, implicating ADAM17 as a major regulator of AR in the liver. EGFR activation is key to hepatocyte cell cycle progression, and rodents in which liver EGFR is conditionally inactivated have impaired liver regeneration after PH (28,29). TGF-␣ and HB-EGF, which are other EGFR ligands and hepatocyte mitogens, are also cleaved by ADAM17 in cell culture (32).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these hyperacetylated genes are known to be induced during, to positively regulate, or to interact with factors that promote liver regeneration. For example, Ccnd1 (i.e., cyclin d1), Cdkn1a (i.e., p21), Gadd45g, Lcn2, and Myc are induced in early regenerating liver [4][5][6][7] ; Ccnd1, Egfr, and Prlr promote liver regeneration [8][9][10][11] ; and Tcf7l2 (also known as Tcf4) binds to b-catenin, whose signaling is activated during and promotes regeneration. 12 Deacetylated genes Similar examination of genes deacetylated in response to PH showed 37 of 392 associated with cell cycle-and 31 linked to cell death-related gene category terms ( Tables 1 and 2).…”
Section: Functional Classification Of Regenerative Changes In Liver Hmentioning
confidence: 99%